Management 3.0: A Systematic Literature Review and Research Agenda - Fernando Almeida; Eduardo Espinheira (Program Studi S3 Ilmu Manajemen, 2021)
Management 3.0 is a new concept that intends to revolutionize the way managers and leaders act within companies to offer a more happy, collaborative, and productive work environment. This paper aims to analyze the management 3.0 phenomenon and establish a research agenda in the field. A systematic review was conducted considering 215 published studies in the field between 2010 and 2019. The findings reveal that management 3.0 is an emerging area and one that has grown in 2019 and involves multidisciplinary research teams from management, leadership, information technology, and psychology.